HUBUNGAN KOORDINASI MATA TANGAN DAN POWER OTOT LENGAN BAHU TERHADAP HASIL SERVIS PANJANG SISWA YANG MENGIKUTI EKSTRAKURIKULER BULUTANGKIS DI SMA NEGERI 1 SABAK AUH KABUPATEN SIAK - Doni Kurniawan; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted with the aim to determine the relationship of eye hand coordination and shoulder arm muscle power to the results of long service students who take extracurricular activities at SMA Negeri 1 Sabak Auh Siak Regency. The problems found in this Research are eye hand and muscle power coordination of the shoulder arms are still not optimal, it is seen when students do badminton long service, students look stiff when swinging the arm as a result the shoulder strength will be reduced then the ball is out of control again, losing direction of the goal so the ball hangs in and out to the side of the court. This research was conducted in the multipurpose building SMA Negeri 1 Sabak Auh. BOB Kampung Belading Street, Kec.Sabak Auh, Siak district, Riau was conducted in February to September 2019. The sampling technique used in this Research was total sampling, in which a total population of 10 people was selected as a sample. Based on the results of the Research that the author has described in the previous chapter, the following conclusions can be drawn: